Eight cycles of recurrent selection for resistance to angular leaf spot in common bean - Arantes,Lúcio de Oliveira (2010)
The genetic progress (GP) was evaluated after eight cycles of recurrent selection for resistance to angular leaf spot in common bean and indirect gain for yield and grain type. The base population (Cycle-0) was obtained from the diallel cross of seven lines with carioca grain and ten resistance sources. To obtain Cycle I, the most resistant S0 plants of Cycle 0 were intercrossed. The same procedure was adopted in the subsequent cycles. GP for resistance to the pathogen was estimated by the overall average of the progenies of each cycle in comparison with control Carioca MG and for productivity in comparison to the controls Carioca MG and Pérola. Lines of the first six cycles were used for grain type. No GP was detected for resistance to angular leaf spot. However, the indirect yield gain was 2.3% and 2.5% in the selection for grain type, with values similar to those obtained by direct selection for these traits.